2004
DOI: 10.1111/j.1365-3040.2003.01139.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of ion channels in the protoplasts of the Mediterranean seagrass Posidonia oceanica

Abstract: Posidonia oceanica (L) Delile, a seagrass endemic of the Mediterranean sea, provides food and shelter to marine organisms. As environment contamination and variation in physico-chemical parameters may compromise the survival of the few Posidonia genotypes living in the Mediterranean, comprehending the molecular mechanisms controlling Posidonia growth and development is increasingly important. In the present study the properties of ion channels in P. oceanica plasma membranes studied by the patch-clamp techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…In seagrasses, which tolerate very high Na + concentrations, this would imply very high salt concentrations within the cell, especially in the vacuole, in which high salinity is more compatible with metabolism than in the cytoplasm (Tyerman 1980). Strong Na + accumulation in the vacuoles of leaf parenchyma cells is probably related to the activity of Na + -permeable ion channels (Carpaneto et al 1997). In this respect, it is conceivable that the occurrence of tonoplast aquaporins contributes to adjust the osmotic gradient in seagrasses, as it does in terrestrial plants.…”
Section: Characterization Of Two P Oceanica Aquaporin-encoding Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…In seagrasses, which tolerate very high Na + concentrations, this would imply very high salt concentrations within the cell, especially in the vacuole, in which high salinity is more compatible with metabolism than in the cytoplasm (Tyerman 1980). Strong Na + accumulation in the vacuoles of leaf parenchyma cells is probably related to the activity of Na + -permeable ion channels (Carpaneto et al 1997). In this respect, it is conceivable that the occurrence of tonoplast aquaporins contributes to adjust the osmotic gradient in seagrasses, as it does in terrestrial plants.…”
Section: Characterization Of Two P Oceanica Aquaporin-encoding Genesmentioning
confidence: 99%
“…At cellular level, the main role in determining osmotic gradient is related to ion channels (Carpaneto et al 2004); however, adjustment of such gradient can be related also to water transport through aquaporins, whose efficiency can be modulated either by post-translational modifications or by modulation of aquaporin gene transcription and translation (Maurel et al 1997).…”
Section: Expression Of Aquaporin Genes In Vivo and In Response To Chamentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Na + accumulation in shoots was accompanied by a significant decrease in K + concentrations. It has been suggested that Na + and K + compete for uptake at the plasma membrane level (Carpaneto et al, 2004). Hence, limited absorption of potassium impairs plant growth and development as this cation functions as a cofactor of various reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Patchclamp research on higher plant species was first reported in 1984 (Schroeder et al 1984). However, the application to marine algae and plants is limited to Valonia utricularis (Heidecker et al 1999;Binder et al 2003), Coccolithus pelagicus (Taylor and Brownlee 2003) and Posidonia oceanica (Carpaneto et al 2004).…”
Section: Introductionmentioning
confidence: 98%